A REVIEW OF FORENSIC ENTOMOLOGY CASES AT IPOH HOSPITAL AND HOSPITAL UNIVERSITI KEBANGSAAN MALAYSIA FOR THE YEAR 2003 - Firdaus Mohd Salleh, Ahmad; Abdullah Marwi, Mohamad; Jeffery, John; Afandy Abd, Nor; -, Hamid; Muhd Zuha, Raja; Omar, Baharudin (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2008)
Forensic entomology was utilized to determine the postmortem interval of eleven forensic cases sentfor autopsy examination at Ipoh Hospital and Hospital University Kebangsaan Malaysia between of Januaryto December 2003. Sixth species of sarcosaprophagous flies: Chrysomya megacephala, Chrysomya rufifacies,Chrysomya villeneuvi, Chrysomya nigripes, Synthesiomya nudiseta and a sarcophagid fly were found amongthe maggot specimens received by the Forensic Entomology Laboratory, Department of Parasitology &Medical Entomology, Universiti Kebangsaan Malaysia. Those maggots were collected from dead bodiesfound among others in wrapped in gunny bags, around water tank, hanged with black nylon clothes, insidehome, beside road, drowning in lombong and an estate. Ch. megacephala was the main species found in eightcases examined. Postmortem Interval (PMI) estimated from the cases varied from one day to 10 days.
Keywords: Forensic entomology, post-mortem interval, decomposing bodies